2023
DOI: 10.3390/biology12030390
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of COVID-19 on New Lung Cancer Diagnoses, by Stage and Treatment, in Northern Italy

Abstract: The COVID-19 pandemic has had a significant impact on new cancer diagnoses. This study aims to evaluate the implications of the lockdown period on new lung cancer diagnoses in northern Italy. We compared 2020 with 2019 cancer registry data, reporting the variations by age, stage, and treatments. In 2020, 303 lung cancer cases were registered, 21 fewer than in 2019. Cases fell in men (−31 patients, 9.6%) but not in women (+10 patients, +3.1%). A significant drop in stage I from 19.8% to 12.9% (p < 0.05) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…A study in northern Italy found a 6.5% decrease in lung cancer diagnoses in 2020, compared with 2019. 10 Results differed by sex, with a decrease among males (−9.6%) but not females (+3.1%). 10 In addition, there was a decrease in diagnosis of stage 1 disease (19.8% v. 12.9%) with an associated increase in diagnosis of stage III disease (12.7% v. 19.1%).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A study in northern Italy found a 6.5% decrease in lung cancer diagnoses in 2020, compared with 2019. 10 Results differed by sex, with a decrease among males (−9.6%) but not females (+3.1%). 10 In addition, there was a decrease in diagnosis of stage 1 disease (19.8% v. 12.9%) with an associated increase in diagnosis of stage III disease (12.7% v. 19.1%).…”
Section: Discussionmentioning
confidence: 91%
“… 10 In addition, there was a decrease in diagnosis of stage 1 disease (19.8% v. 12.9%) with an associated increase in diagnosis of stage III disease (12.7% v. 19.1%). 10 Surgery decreased from 28.7% to 21.5% and chemotherapy increased from 17.6% to 34.3%. 10 …”
Section: Discussionmentioning
confidence: 93%